Desempenho, características das fibras musculares e das carcaças de cordeiros ½ Dorper Santa Inês abatidos com diferentes pesos - Dias, Franciane Barbiéri (2009)
The objective of this work was to evalute the influence of slaughter weight, sex and type of delivery of performance, characteristics of muscle fibers and carcasses of ½ Dorper Santa Inês lambs. Ther were used 23 ½ Dorper ½ Santa Inês lambs, 11 not castrated males and 12 females, with average weight of 19.39 ± 2.54 kg, randomly assigned to three treatments (P28, P32 and P36 kg). The animals were weighed and, when they reached the weight determined by the corresponding treatment, they were slaughtered. There was no significant difference (P>0,05) on the frequency of SO fibers (slow oxidative), FOG fibers (fast oxidative glycolytic) and FG fibers (fast glycolytic) of the Semitendinosus muscle of lambs, according to slaughter weight, sex and type of delivery. The means of SO, FOG and FG fiber diameters, did not show significant differences (P>0,05) for treatment and type of delivery, but differ with respect to sex in SO fibers. The means of average daily weight gain (WDG), weight loss by cooking (WLC) and shear force (SF) of lambs slaughtered with different weights did not show significant differences (P>0,05) for treatment, sex and type of delivery. The frequency of muscle fibers, the ADG, WLC and SF were not affected by the following variables: weight of slaughter, sex and type of delivery in ½ Dorper ½ Santa Inês lambs. The sex influenced the fibers diameter of type SO, in which the males had the higher measures. The means for body condition, subcutaneous fat, fat color and meat color were 2,83; 2,81; 1,85 and 1,58, respectively. The meat color was influenced (P <0.05) by sex, especially the females with higher scores, with an average of 1,71. The means for non carcass components yield (blood, skin, full gastrointestinal tract, empty gastrointestinal tract, spleen, liver, heart, lungs+trachea and feet) did not show significant differences between treatments (P> 0,05). The yield of first and second cuts did not show significant differences (P> 0,05) for slaughter weight, type of delivery and sex. The yields of thirds did showed significant differences (P <0,05) for slaughter weight, but did not differ in the type of delivery and sex. For percentage of bone, muscle and fat there were not significant differences (P>0,05) according to slaughter weight, type of delivery and sex. Under conditions in which the work was performed or female lambs of single or dual delivery may be slaughtered between 28 to 36 kg body weights, but the slaughter of lambs with higher weights should be carefully evaluated, it interferes with the termination cost.